Structure based assessment of quality of WEB sites - Sai Virajitha, V; JKR Sastry, Dr; V Chandra Prakash, Dr; Srija, P; Varun, M (International Journal of Engineering and Technology, 2018)
WEB sites are playing very vital role in information dissemination. Most of the businesses are using their WEB sites to promote market and conduct business. The quality of the WEB sites has indirect relationship with quantum of business conduct by the industrial establishments. Quality of a web site is based on number of characteristics; computation of the same in quantitative terms is a complex process. Structure of a WEB site plays a vital role in hosting the content in most comprehensive manner.In this paper the subjecting of the WEB to data mining and determining the structures contained in the WEB site is presented. The structures are evaluated to find the quality of the same individually and also combined considering all the structures that are mined. A method is presented in this paper using which the quality of a web site is computed considering the structure of the WEB site alone.Â